How Passionate People Seek and Share Various Forms of Information in Their Serious Leisure. Issue 1 (2nd January 2020) - Mansourian, Yazdan
ABSTRACT: This paper presents an analytical review of the existing literature about Human Information Behaviour (HIB) in the context of Serious Leisure (SL). Various forms of information activities in this context have been identified and categorised to depict common patterns in information seeking and sharing. The findings show the informational aspect of SL is a rich and productive topic in HIB because it entails the continuous pursuit and recreation of knowledge and often involves several types of information-related actions including information seeking, searching, browsing, retrieving, gathering, saving, organising, sharing, evaluating, measuring, analysing, producing and disseminating. The paper also presents a tentative model of predominant information sources in SL based on the analytical literature review and theoretical speculation. This preliminary model categorises SL activities into three main groups including (1) intellectual pursuits, (2) creating or collecting physical objects/materials/products and (3) experiential activities. Similarly, the paper categorises SL participants into three major groups of appreciators, producers/collectors and performers. Each category has its own priorities, source preferences and information behaviour. The findings also indicate that exploring various aspects of HIB in the SL domain is still an emerging ground and that the majority of studies have been thus far been qualitative. As a result, further research needs to be done to gain a more comprehensive picture of this area and to validate the growing knowledge base with larger samples and further settings.